BILINGUAL DALAM PERISTIWA JUAL BELI DI PASAR RAKYAT - Ermi Ramadhani; Sri Suryana Dinar; sulfiah (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2024)
Code mixing occurs in many forms and is influenced by several conditions; this study seeks to characterize these forms and their effects in the speech events of vendors and customers at the Penanggo People's Market in Lambandia District, East Kolaka Regency. This study takes a sociolinguistic approach to its qualitative descriptive research. A variety of listening, note-taking, recording, and interviewing strategies were employed in this investigation. This study's data analysis procedure involves transcribing spoken information into written form in Indonesian, then back into spoken form, and finally collecting the data based on its meaning characteristics. Examining the causes of code mixing is the next step. Findings from this research include instances of code mixing as well as other kinds of code mixing, such as the insertion of words, phrases, and clauses. Code mixing can occur due to the following factors: 1) the code's limitations, 2) the speaker's personality and function, 3) the speaker's goal, and 4) the speaker's background.